UTILIZATION OF COFFEE HUSK WASTE INTO BRIQUETTES AS AN ENVIRONMENTALLY FRIENDLY ALTERNATIVE ENERGY SOURCE IN NGAREANAK VILLAGE - Muqorobiin, Miftahhul; M. Burhan Rubai Wijaya; Sevira Naza Anatasya; Syafira Prameswari Ardhani (Jurnal Saintifik (Multi Science Journal), 2025)
In Ngareanak Village, Singorojo Sub-district, Kendal Regency, most coffee husk waste remains unused, often piled up or burned, causing potential environmental pollution. Through a community service program, the GIAT KKN UNNES 12 team introduced the utilization of coffee husk waste into briquettes as an eco-friendly alternative energy source. The activities included surveys, experiments, and training for local communities. Results showed that the PKK women’s group successfully produced briquettes with high calorific value, stable combustion, and low ash residue. This innovation is expected to enhance community skills and create opportunities in renewable energy-based enterprises.